2018
DOI: 10.1371/journal.pmed.1002640
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and risk of Parkinson disease: A nationwide cohort study

Abstract: BackgroundThe association of metabolic syndrome (MetS) with the development of Parkinson disease (PD) is currently unclear. We sought to determine whether MetS and its components are associated with the risk of incident PD using large-scale cohort data for the whole South Korean population.Methods and findingsHealth checkup data of 17,163,560 individuals aged ≥40 years provided by the National Health Insurance Service (NHIS) of South Korea between January 1, 2009, and December 31, 2012, were included, and part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
102
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 44 publications
4
102
0
1
Order By: Relevance
“…interactions between serum GGt and obesity or metabolic syndrome and the risk of pD. In our population, both obesity and metabolic syndrome increased PD risk in both sexes (Tables 3 and 4), which was in line with previous reports 10 . Interestingly, the impact of both obesity and metabolic syndrome was higher in women than in men (adjusted HR = 1.22 (95% CI: 1.17-1.28) vs. 1.10 (95% CI: 1.05-1.15) and adjusted HR = 1.69 (95% CI: 1.61-1.77) vs. 1.34 (95% CI: 1.28-1.41) for women and men, respectively).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…interactions between serum GGt and obesity or metabolic syndrome and the risk of pD. In our population, both obesity and metabolic syndrome increased PD risk in both sexes (Tables 3 and 4), which was in line with previous reports 10 . Interestingly, the impact of both obesity and metabolic syndrome was higher in women than in men (adjusted HR = 1.22 (95% CI: 1.17-1.28) vs. 1.10 (95% CI: 1.05-1.15) and adjusted HR = 1.69 (95% CI: 1.61-1.77) vs. 1.34 (95% CI: 1.28-1.41) for women and men, respectively).…”
supporting
confidence: 93%
“…Furthermore, weight loss that could occur during the early course of PD 29,30 might affect the risk estimation because this study was conducted with a relatively short follow-up period (median 6.4 years); therefore, the individuals who had already developed pathological changes in their body but were diagnosed with PD only after developing overt clinical signs later, might have been included in the initial population, even though we applied a 1-year lag period. Several prospective cohort studies reported the relationship between metabolic syndrome and the future risk of PD 10,31 . One nationwide cohort analysis showed that metabolic syndrome increased the risk of PD.…”
Section: Discussionmentioning
confidence: 99%
“…If proved to be true in humans, these findings may have great clinical implications. Elderly people are usually at high risk of developing osteoporosis, cognitive function deficit, sarcopenia, and PD; patients with glucose-related disorders, such as diabetes and metabolic syndrome are also prone to suffer cognitive decline or PD [97][98][99]; and older adults with motoric cognitive risk syndrome, a recently described predementia syndrome characterized by slow gait with cognitive complaints, has been implicated as a major predictor of cognitive decline and dementia [100], thus, could all these disorders have the common soil, that is, lack of OCN? Or collectively, could we simply name them as "Osteocalcin Syndrome" or "Osteocalcinopathy"?…”
Section: Future Directionsmentioning
confidence: 99%
“…However, other symptoms such as anosmia (loss of smell) (Omori and Okutani, 2019), constipation (Lubomski et al, 2019), sleep disorders (specifically rapid eye movement behavior sleep disorder) (Postuma et al, 2019), and depression (Bayram et al, 2019) also emerge well before motor impairments. Recently, several studies pointed to the fact that even before emergence of motor and non-motor symptoms, pathogenesis begins with metabolic abnormalities occurring at different levels of neural hierarchy: subcellular, cellular and network levels (Bolam and Pissadaki, 2012;Limphaibool et al, 2018;Muddapu et al, 2019;Nam et al, 2018;Pacelli et al, 2015;Pissadaki and Bolam, 2013). With the help of a computational model, Muddapu et al (Muddapu et al, 2019) have recently suggested that the excitotoxic loss of SNc cells might be due to energy deficiencies occurring at different levels in the neural hierarchy.…”
Section: Introductionmentioning
confidence: 99%